An analysis of the supply-side factors of geological exploration in China based on provincial panel data between 1999 and 2017. (June 2022) - Zhang, Zhimin; Elshkaki, Ayman
Abstract: Geological exploration inputs' appropriateness is questionable and becomes one of research hotspots in the supply-side reform of geological exploration industry, as China has increased its investment in geological exploration in recent years to secure needed resources. In this study, starting with three theoretical hypotheses, we have constructed transmission chain of geological exploration value with mineral exploration as the core to analyze the appropriateness of the geological exploration inputs, and solve the problem that geological exploration products can't effectively measure their output benefits due to their quasi-public product attributes. To verify the theoretical framework, the effect of geological exploration inputs on mineral outputs and stockpiling has been examined using the Chinese provincial panel data between 1999 and 2017 and the stochastic frontier model. The results show that the investment and exploration rights are excessive, while labor is not, and the excessive investment is caused by fiscal overinvestment. In terms of policy, the government should appropriately reduce fiscal investment in mineral exploration, and gradually withdraw from the commercial mineral exploration sector. The key to improve the effectiveness supply of geological exploration factors' market is to establish a sound market for venture exploration capital and exploration technology services. Graphical abstract: Image 1 Highlights: Mineral exploration was the core of the transmission chain of geological exploration value in China. Balance panel data have been used to investigate whether geological exploration input is excessive. There is a significant positive correlation between geological exploration input and mineral raw ore output. The geological exploration investment and exploration rights were excessive, and labor was not. Excessive fiscal investment leads to overinvestment in geological exploration.